Three-Dimensional Speckle Tracking Echocardiography for Detection of Acute Coronary Occlusions in Non-ST-Elevation Acute Coronary Syndrome Patients - Thomas M. Stokke; Kristina H. Haugaa; Kristoffer Russell; Thor Edvardsen; Sebastian I. Sarvari (Diagnostics)
Objectives: This study aimed to evaluate the ability of three-dimensional (3D) speckle tracking echocardiography (STE) to detect acute coronary occlusions in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS) and its potential diagnostic advantage over two-dimensional (2D) STE. Methods: Fifty-six patients with NSTE-ACS (mean age 64 ± 11 years; 80% male) underwent 2D and 3D transthoracic echocardiography prior to coronary angiography. Global longitudinal strain (GLS), global circumferential strain (GCS), and 3D ejection fraction (EF) were analyzed. Acute coronary occlusion was defined as TIMI flow 0–1 in the presumed culprit artery. Results: Acute coronary occlusion was present in 16 patients (29%). Patients with occlusion had significantly more impaired strain compared to those without: 3D GLS (−12.5 ± 2.7% vs. −15.5 ± 2.1%, p < 0.001), 2D GLS (−12.6 ± 2.8% vs. −15.6 ± 2.0%, p < 0.001), 3D GCS (−24.8 ± 4.4% vs. −27.8 ± 4.3%, p = 0.02), and 2D GCS (−18.1 ± 5.5% vs. −22.9 ± 4.7%, p = 0.002). In contrast, 3D EF did not differ significantly between groups (52.5 ± 4.7% vs. 54.7 ± 5.7%, p = 0.16). Receiver operating characteristic analysis showed that 3D and 2D GLS had the highest diagnostic performance (AUCs 0.81 and 0.78), while 3D EF had the lowest (AUC 0.61). Feasibility was lower for 3D STE (86%) than for 2D longitudinal strain (95%, p = 0.03). Conclusions: Both 3D and 2D GLS showed higher diagnostic accuracy than 3D EF in identifying acute coronary occlusion in NSTE-ACS patients. While 3D STE enables simultaneous assessment of multiple parameters, it did not offer incremental diagnostic value over 2D STE and had lower feasibility.